Expressão diferencial de genes normalizadores e da família LTPs1, em genótipos de arroz sob estresse salino - Moraes, Gabriela Peres (2013)
On the production of rice, the salinization of the soil and the water of irrigation, during the establishment phases its closely related to the variation in the levels of production. Among the main damages caused by saline stress at cellular level, are the disturbances in the plasmatic membrane, being its effects manifested by alterations on the permeability, lipid composition, electrical potential and activity of proteins linked to it. The proteins LTPs ("Lipid Transfer Proteins") are related to the transfer and connection of fatty acids and phospholipids between membranes, in addition to being involved in the modification of the lipid composition and their biogenesis. On this note, the objective of this work was to analyze the expression of ten candidate genes to normalizing for studies of genetic expression and verify the differential expression of eleven genes LTPs in rice seedlings. The genotypes BRS Bojuru (tolerant) and BRS Ligeirinho (sensitive) were exposed to 150mM of NaCl in times 0, 24, 48, 72 and 96 hours. The normalizing gene UBQ10 was the most stable for these experimental conditions tested, while the least stable were IF-4a, Tip41-Like and Cyclophilin, being, therefore not in, the least indicated. Among the analyzed LTPs genes, LTP10 presented a high expression value (70 times more) in the 96 hour of stress, when compared to the control in sensitive genotype. For the BRS Bojuru this same gene kept the expression standards while exposed in different times to the stress. The gene LTP14 showed similar patterns of expression between the genotypes studied. In the beginning of the stress, the level of expression practically unaltered, followed by increase and successive decrease after 72 hrs of salt exposure. After the correlation analysis, it was observed that LTP7 and 14 showed a positive correlation, while LTPs 10,26 and 23 showed negative correlation among genotypes. The phylogenetic tree showed a grouping tendency similar to the nucleotides and amino acids sequences analyzed. Based on the results of this study, it was concluded that the gene UBQ10 is the best normalizing for the experimental conditions tested and the genes LTP10, 23 and 26 can be used as a marker for the assisted selection of rice plants for the saline stress for showing contrasting response of expression between genotypes.